2013
DOI: 10.1149/2.005305jes
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Electrochemical Properties of Self-Organized Titanium Dioxide Nanotubes in Lithium Batteries by Surface Polyacrylonitrile Electropolymerization

Abstract: The surface of the amorphous TiO 2 nanotubes is critical to achieve high capacity, cycling stability and high rate performance. In order to improve the stability of nanotubular titanium dioxide electrodes in lithium batteries, polyacrylonitrile (PAN) has been deposited by electropolymerization. Self-organized TiO 2 nanotubes were prepared by titanium anodization with different aspect ratios. After electropolymerization, electron microscopy, composition mapping and XPS data confirmed that electrododeposited PAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
(70 reference statements)
0
12
0
Order By: Relevance
“…2 The possible formation of a passivating film that avoids the consumption of electrolyte on the surface of nt-TiO 2 is not wholly confirmed, but several studies have inferred its existence. 2,37 In order to achieve high power batteries, the retention of the capacity at high current density is critical. Thus, we have studied the cycling at several current densities (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The possible formation of a passivating film that avoids the consumption of electrolyte on the surface of nt-TiO 2 is not wholly confirmed, but several studies have inferred its existence. 2,37 In order to achieve high power batteries, the retention of the capacity at high current density is critical. Thus, we have studied the cycling at several current densities (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Two main mechanisms can contribute to the reversible capacity of amorphous nt-TiO 2 . 2,6 One of these mechanisms is the lithium insertion into TiO 2 with the consequent reduction from Ti 4+ to Ti 3+ , typically up to x = 0.5 in anatase-type Li x TiO 2 although x may be larger for amorphous titania. The electrochemical Li insertion into anatase leads to two two-phase regions: first the anatase/Lititanate (α/β) coexistence, and second the phase coexistence between Li-titanate and the Li 1 TiO 2 phase (β/γ).…”
mentioning
confidence: 99%
“…Djenizian and co‐workers have studied the lithium storage behaviour of self‐organised TiO 2 nanotubes coated with a layer of room‐temperature Li + ‐conducting gel‐type PEO‐PMMA copolymer (see Figure 33 a–d) 39b. 149b, 156 Nacimiento et al 157. have shown that improvements in the lithium storage behaviour of self‐organised TiO 2 nanotubes can be obtained by coating the nanotubes with Li + ‐conducting polyacrylonitrile through the use of electropolymerisation.…”
Section: Titania Versus Nanostructured Titaniamentioning
confidence: 99%
“…The plots clearly show that the diameter of the semicircle of the graphene/GeO 2 microtubes is much smaller than that of the pure GeO 2 electrode, indicating that the presence of graphene enhances the charge transfer process compared to pure GeO 2 . The results are fitted according to an equivalent circuit [Re (Rct CPE1) CPE2], where Re represents the effective series resistances of the electrode, electrolyte and separator, Rct is the Faradic charge‐transfer resistance, and CPE1 and CPE2 are constant phase elements 32, 34. The fitting results yield effective series resistances of graphene/GeO 2 and pure GeO 2 electrodes of 16 and 22 Ω, respectively.…”
mentioning
confidence: 99%